ZmMKK3, a novel maize group B mitogen-activated protein kinase kinase gene, mediates osmotic stress and ABA signal responses - Zhang, Maoying (Journal of plant physiology, 2012)
Copyright © 2012 Elsevier GmbH. All rights reserved.